2019
DOI: 10.21203/rs.2.10361/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bibliometric Analysis of Global Sickle Cell Disease Research From 1997 – 2017

Abstract: Background: Sickle cell disease (SCD) is an autosomal recessive genetic disease caused by single point mutation in the β-globin chain of the hemoglobin. It has been recognized by World Health Organization as a public health priority since 2006. Methods: Scopus database was used in this study with the search descriptors: “sickle cell” and “sickle cell disease”. We applied common bibliometric indicators to evaluate the trend in scientific literature in sickle cell disease research. Results: We retrieved a total … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…In agreement with our result, Okoroiwu et al identified "Vichinsky, E.P." as the most contributing author in SCD research; however, Musaa et al identified "Serjeant GR" as the most productive author [6,7]. Highlighting the most contributing authors in ACS may help investigators around the world plan future directions and collaborations.…”
Section: Publications Trendssupporting
confidence: 90%
See 4 more Smart Citations
“…In agreement with our result, Okoroiwu et al identified "Vichinsky, E.P." as the most contributing author in SCD research; however, Musaa et al identified "Serjeant GR" as the most productive author [6,7]. Highlighting the most contributing authors in ACS may help investigators around the world plan future directions and collaborations.…”
Section: Publications Trendssupporting
confidence: 90%
“…The largest number of publications were published in "Blood" and "American Journal of Hematology," with nine articles each. In concordance, previous bibliometric analyses identified these two journals as the most productive journals in SCD [6,7]. Hence, these journals could be recommended for investigators interested in this field.…”
Section: Publications Trendssupporting
confidence: 81%
See 3 more Smart Citations